2017
DOI: 10.1002/chem.201704501
|View full text |Cite
|
Sign up to set email alerts
|

A Superior Synthesis of Longitudinally Twisted Acenes

Abstract: Seven longitudinally twisted acenes (an anthracene, two tetracenes,t hree pentacenes, and ah exacene) have been synthesizedb yt he addition of aryllithium reagents to the appropriate quinone precursors, followed by SnCl 2 -mediatedr eductiono ft heir diol intermediates, and severalo ft hese acenesh ave been crystallographicallyc haracterized. The new syntheses of the three previously reported twisted acenes, decaphenylanthracene (1), 9,10,11,20,21,22-hexaphenyltetrabenzo[a,c,l,n]pentacene( 2), and 9, 10,11,12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Indeed, this new torque‐lock‐propagate approach is modular and versatile and can readily be used to make a wide range of heli‐acenes of variable length with a spectrum of substituents on the acene domain. Its potential as a powerful twisted‐acene synthetic approach can be extended even further when coupled with new acene homologation methods such as those reported by the Kilway group [31, 43] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this new torque‐lock‐propagate approach is modular and versatile and can readily be used to make a wide range of heli‐acenes of variable length with a spectrum of substituents on the acene domain. Its potential as a powerful twisted‐acene synthetic approach can be extended even further when coupled with new acene homologation methods such as those reported by the Kilway group [31, 43] …”
Section: Discussionmentioning
confidence: 99%
“…Its potential as a powerful twisted-acene synthetic approach can be extended even further when coupled with new acene homologation methods such as those reported by the Kilway group. [31,43] Experimental Section General information: All computational studies were make using either the Gaussian 09 or 16 software packages. All energy minima (S o , S 1 , and T 1 ) had zero negative frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we described the rather facile synthesis of compound 3 by the addition of phenyllithium to an appropriate quinone precursor, followed by SnCl 2 ‐mediated reduction of the diol intermediate. The number of synthetic steps was reduced to three, and the overall yield was improved by 24‐fold . This result indicated that a reasonable route to hexacene 4 might be at hand.…”
Section: Figurementioning
confidence: 98%
“…For us, heating phencyclone ( 5 ) with naphthazarin ( 6 ) in nitrobenzene did not form the desired 11,14‐dihydroxy‐9,16‐diphenyldibenzo[ a , c ]tetracene‐10,15‐dione ( 7 ) in any appreciable amount—if at all, the majority of the product formed was a black solid that has yet to be identified. Why this is the case is not clear and made all the more curious by the fact that heating a mixture of 5 with 5,8‐dioxo‐5,8‐dihydronaphthalene‐1,4‐diyl diacetate ( 8 ) in nitrobenzene did form 7 , which was conveniently and cleanly precipitated from the reaction contents in 33 % yield by the addition of acetone (Scheme ).…”
Section: Figurementioning
confidence: 99%
“…1 Stannous chloride (SnCl 2 ) is a mild Lewis acid that is widely used as a reducing agent and catalyst in various synthetic organic operations and in the production of biodegradable polylactic acid. [2][3][4] In inorganic synthesis, SnCl 2 , which acts as an effective reducing agent, could reduce metal salts, such as silver and gold salts to their metals, Cu 2+ to Cu + , and Fe 3+ to Fe 2+ . 5 Particularly, Sn 2+ species have been used in articles of daily use, such as tinplating of steel to make tin cans, 6 added to some canned and bottled foods, 7 and mouth wash. 8 In additional, tin is an essential trace micronutrient for living organisms.…”
Section: Introductionmentioning
confidence: 99%